2021
DOI: 10.1007/s12665-021-09449-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of percolated reclaimed water from river-channel reservoir on groundwater using tracers in Beijing, Northern China

Abstract: As an increasingly important aspect of water management, historical dry river-channels, ponds or lakes are operated for the storage of reclaimed water as a landscape with the need for reuse of water. However, the percolated reclaimed water may have an adverse effect on groundwater quality. The aims of this work are to evaluate the potential for using various groundwater constituents or characteristics as tracers of percolated reclaimed water, to clarify the groundwater hydrochemical process with the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In both SNWRA and RWRA, the number of total PMTs first increased and then decreased with the sampling depth and reached the peak at −80 m (Figure S5). Due to the presence of thick silty clay, the hydraulic connection between the aquifers at −80 and −150 m was weak . It is suggested that the surface water vertically entered the aquifer at −80 m after flowing through the aquifers at −30 and −50 m, and the infiltration was limited further downward.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both SNWRA and RWRA, the number of total PMTs first increased and then decreased with the sampling depth and reached the peak at −80 m (Figure S5). Due to the presence of thick silty clay, the hydraulic connection between the aquifers at −80 and −150 m was weak . It is suggested that the surface water vertically entered the aquifer at −80 m after flowing through the aquifers at −30 and −50 m, and the infiltration was limited further downward.…”
Section: Resultsmentioning
confidence: 99%
“…The four aquifers are targeted aquifers for AGR. The aquifer sediments are dominated by gravel and sand, interlayered with silty clay, with increase in the proportion of silty clay in deep aquifers, and hydraulic conductivity of aquifer is around from 6.9 × 10 –4 to 1.2 × 10 –3 m/s . The vadose zone with relatively high permeability provides a vertical recharge pathway of surface water to shallow aquifers .…”
Section: Methodsmentioning
confidence: 99%
“…The solute transport model was developed based on the groundwater ow model. Cl − as a conservative solute has been generally used to trace and evaluate the impact of RW recharge on subsurface ow systems (Yu et al, 2016;Zhang and Yu, 2021). Cl − concentrations of RW are usually higher than that in natural water.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The pH value of mine water is often low, accompanied by a large number of ferrous ions, which increases the difficulty of its treatment. The water quality characteristics of mine water with high calcium and magnesium ions, high carbonate ions, and high sulfate ions will cause it to be very easy to scale in the circulating cooling system, where the formation of sulfate scale is difficult to be removed by conventional methods 1–8 …”
Section: Introductionmentioning
confidence: 99%
“…The water quality characteristics of mine water with high calcium and magnesium ions, high carbonate ions, and high sulfate ions will cause it to be very easy to scale in the circulating cooling system, where the formation of sulfate scale is difficult to be removed by conventional methods. [1][2][3][4][5][6][7][8] In circulating cooling water systems, the following types of scale may be generated: carbonate scale, sulfate scale, and silicate scale.…”
Section: Introductionmentioning
confidence: 99%